Effect of Oral Allylnitrile Administration on Cochlear Functioning in Mice Following Comparison of Different Anesthetics for Hearing Assessment - Verdoodt, Dorien; Eens, Sander; Van Dam, Debby; De Deyn, Peter Paul; Vanderveken, Olivier M.; Szewczyk, Krystyna; Saldien, Vera; Ponsaerts, Peter; Van Rompaey, Vincent (Frontiers in Toxicology, 2021)
Background: Allylnitrile is a compound found in cruciferous vegetables and has the same lethality and toxic effects as the other nitriles. In 2013, a viable allylnitrile ototoxicity mouse model was established. The toxicity of allylnitrile was limited through inhibition of CYP2E1 with trans-1,2-dichloroethylene (TDCE). The allylnitrile intoxication model has been extensively tested in the 129S1 mouse strain for vestibular function, which showed significant HC loss in the vestibular organ accompanied by severe behavioural abnormalities. However, the effect of allylnitrile on auditory function remains to be evaluated. Commonly used anaesthetics to conduct hearing measurements are isoflurane and ketamine/xylazine anaesthesia but the effect of these anaesthetics on hearing assessment is still unknown. In this study we will evaluate the otovestibular effects of oral allylnitrile administration in mice. In addition, we will compare the influence of isoflurane and ketamine/xylazine anaesthesia on hearing thresholds. Methods and Materials: Fourteen Coch+/- CBACa mice were randomly allocated into an allylnitrile (n=8) and a control group (n=6). Baseline measurements were done with isoflurane and one week later under ketamine/xylazine anaesthesia. After baseline audiovestibular measurements, mice were co-administered with a single dose of allylnitrile and, to reduce systemic toxicity, three intraperitoneal injections of TDCE were given. Hearing loss was evaluated by recordings of auditory brainstem responses (ABR) and distortion product otoacoustic emissions (DPOAE). Specific behavioural test batteries for vestibular function were used to assess alterations in vestibular function. Results: Hearing thresholds were significantly elevated when using isoflurane anaesthesia compared to ketamine/xylazine anaesthesia for all frequencies of the ABR and the mid-to-high frequencies in DPOAE. Allylnitrile-treated mice lacked detectable ABR thresholds at each frequency tested, while DPOAE thresholds were significantly elevated in the low-frequency region of the cochlea and completely lacking in the mid-to high frequency region. Vestibular function was not affected by allylnitrile administration. Conclusion: Isoflurane anaesthesia has a negative confounding effect on the measurement of hearing thresholds in mice. A single oral dose of allylnitrile induced hearing loss but did not significantly alter vestibular function in mice. This is the first study to show that administration of allylnitrile can cause a complete loss of hearing function in mice.